STUDENT ENGAGEMENT : DAMPAK DUKUNGAN GURU DAN SELF REGULATED LEARNING DENGAN MEDIASI MOTIVASI BELAJAR: indonesia - Noer Istsariyah; Saringatun Mudrikah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
This study aims to determine the effect of teacher support and SRL on student engagement, with learning motivation as a mediating variable, among 11th grade Accounting and Institutional Finance students at vocational schools in Sukoharjo Regency. The research approach used is quantitative through a survey method, with PLS-based SEM analysis. The population consists of 322 students, and 178 students were selected as the sample using proportional random sampling. The analysis results indicate that teacher support does not have a significant direct effect on student engagement but significantly influences learning motivation. On the other hand, self-directed learning ability has a significant influence on student motivation and engagement. Learning motivation was also found to significantly mediate the relationship between teacher support and student engagement but did not mediate SRL in learning. This study reinforces the relevance of social cognitive theory and student engagement theory. Teachers are advised to continue providing academic and social support and encourage student independence in learning to enhance their active participation in the classroom.